2016
DOI: 10.1590/s1984-82502016000300004
|View full text |Cite
|
Sign up to set email alerts
|

Green tea glycolic extract-loaded liquid crystal systems: development, characterization and microbiological control

Abstract: Liquid crystal systems (LCSs) have interesting cosmetic applications because of their ability to increase the therapeutic efficiency and solubility of active ingredients. The aim of the present research was to develop green tea glycolic extract-loaded LCSs, to characterize and to perform microbiological control. The ternary phase diagram was constructed using polysorbate 20, silicone glycol copolymer (SGC) , and distilled water with 1.5% glycolic green tea extract. The systems were characterized by polarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Time and excessive amounts of chlorinated compounds are associated with high organic carbon content, and this process results in high concentrations of trihalomethanes, which are considered carcinogenic substances (Marti et al, 2017). Camellia sinensis L. is rich in polyphenols, such as catechins, which account for antioxidant, anti-inflammatory, antifungal, and antimicrobial action (Bernegossi et al 2016;Camargo et al 2016). Some antimicrobial mechanisms of green tea include bacterial cell membrane destruction, enzyme activity inhibition, and inhibition of fatty acid synthesis (Reygaert, 2014).…”
Section: Challenge Test Applied To Vegetables Intentionally Contamina...mentioning
confidence: 99%
“…Time and excessive amounts of chlorinated compounds are associated with high organic carbon content, and this process results in high concentrations of trihalomethanes, which are considered carcinogenic substances (Marti et al, 2017). Camellia sinensis L. is rich in polyphenols, such as catechins, which account for antioxidant, anti-inflammatory, antifungal, and antimicrobial action (Bernegossi et al 2016;Camargo et al 2016). Some antimicrobial mechanisms of green tea include bacterial cell membrane destruction, enzyme activity inhibition, and inhibition of fatty acid synthesis (Reygaert, 2014).…”
Section: Challenge Test Applied To Vegetables Intentionally Contamina...mentioning
confidence: 99%
“…The liquid crystal emulsion is a new type of emulsion which is different from conventional emulsion systems. This system is arranged regularly from surfactant and water molecules formed by the oil-water interface; this arrangement forms an emulsion with a liquid crystal structure which shows better usage than conventional emulsion systems in terms of stability, which is more stable compared to other emulsions because it offers some protection against photo or thermal degradation and increases high cutaneous hydration by increasing water intake in the corneal layer and also can delivering active ingredients with delayed-release in the target area [9]. The formation does not only depend on the emulsion formulation, but also the manufacturing process [10].…”
Section: Introductionmentioning
confidence: 99%
“…The formation does not only depend on the emulsion formulation, but also the manufacturing process [10]. In a previous study, Bernegossi et al [9], had formulated green tea extract into a liquid crystal system using silicone glycol copolymer as a surfactant. The result of the study showed that formulation with a high concentration of surfactants could produce a liquid crystal system with enhanced efficacy of the green tea extract.…”
Section: Introductionmentioning
confidence: 99%